MEDIA KARTU KUARTET DIKDA SENI TARI BERBASIS OUTDOOR LEARNING - Ariyanti, Siti Eva Ariyanti Eva (Joyful Learning Journal, 2020)
Dalam seni tari, guru kelas II SD Negeri 03 Bawu diketahui belum menggunakan media pembelajaran yang inovatif, sehingga diperlukan media yang inovatif dalam pembelajaran. Penelitian ini bertujuan untuk mengembangkan media kartu kuartet DIKDA seni tari berbasis outdoor learning pada materi gerak keseharian dan alam. Untuk mengembangkan media tersebut digunakan penelitian Research and Development (R&D) diadaptasi dari Sugiyono. Penelitian ini diikuti oleh siswa kelas II SD Negeri 03 Bawu berjumlah 41 siswa. Teknik analisis data meliputi analisis data produk, analisis data awal, dan analisis data akhir berupa uji t-tes dan uji n-gain. Hasil pengembangan media kartu kuartet DIKDA Seni Tari berbasis outdoor learning sangat layak digunakan dengan memperoleh hasil persentase sebesar 96,88% oleh ahli media, 96,88% oleh ahli materi dan 93,75% oleh ahli bahasa. Dari hasil skala kecil tanggapan siswa terhadap media sangat baik dengan persentase 100% dan 92% dari tanggapan pada skala besar mendapatkan persentase 97,9% dari siswa dan 100% dari guru. Hasil uji peningkatan rata-rata diperoleh hasil sebesar 0,567 pada skala kecil dan 0,466 pada skala besar. Simpulan penelitian media kartu kuartet DIKDA Seni Tari berbasis outdoor learning materi gerak keseharian dan alam layak dan efektif dalam meningkatkan hasil belajar psikomotorik siswa kelas II Sekolah Dasar. Kata Kunci: Media Pembelajaran; kartu kuartet DIKDA; outdoor learning; Seni Tari In dance education, in the second grade aof Bawu 03 elementary school had not used innovative learning media, so that media development was needed in learning. This research aimed to develop, to find out the results of feasibility, and test the effectiveness of DIKDA quartet cards on dance education based on outdoor learning on daily and natural motion material. The type of this study was Research and Development (R & D) adapted from Sugiyonos theory. The participants of this study were the second grade at Bawu 03 elementary school in the number of 41 students. Data analysis techniques included product data analysis, initial data analysis, and final data analysis in the form of t-test and n-gain test. The results showed that learning media in the media of DIKDA quartet cards on dance education based on outdoor learning was very feasible to use by obtaining a percentage of 96,88% by media experts, 96.88% by material experts and 93,75% by language experts. The results of small scale got a percentage of 100% of students and 92% of teachers and on a large scale get a percentage of 97,9% of students and 100% of teachers. The results of the test large scale got on average obtained results of 0.567 on a small scale and 0.466 on a large scale. The conclusion of this research was the media of DIKDA quartet cards on dance education based on outdoor learning on daily and natural motion material was feasible and effective in improving students psychomotor learning outcomes in the second grade. Keywords: learning media; quartet card DIKDA; outdoor learning; dance education